MENINGKATKAN KEMAMPUAN BERHITUNG AWAL MELALUI PERMAINAN CONGKLAK DI TK AZ-ZAHRA DESA TERAPU KECAMATAN ALUH-ALUH - Ahmad Saidi; Baiti , Noor; yusuf , Muhammad; Nisa, Uswatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine and describe the implementation of the congklak game in enhancing early numeracy skills at Az-Zahra Kindergarten, Terapu Village. This study employed Classroom Action Research (CAR) conducted with a group of 10 children (Group A) at Az-Zahra Kindergarten, Terapu Village. The research was carried out over two cycles comprising four meetings, covering four stages: planning, implementation, observation, and reflection. The results indicate that the use of the congklak game (dakuan/bedakuan) as a learning medium consistently and significantly improved the early numeracy skills of children aged 4–5 years at Az-Zahra Kindergarten across each cycle. Teacher activity improved from the